Pengembangan Bahan Ajar Matematika Berbasis Game Untuk Meningkatkan Minat dan Motivasi Belajar Siswa Dikelas Awal - D.Yuliana Sinaga; Sunggul Pasaribu; Lastiurida siburian (CV Putra Publisher, 2023)
The purpose of developing game-based mathematics teaching materials in the early grades is to increase student motivation and interest in learning and to be able to help students think logically in solving problems. And improve students' ability to apply difficult mathematical concepts. Because there are so many educators who focus more on learning mathematics that use learning resources from textbooks that contain material and formulas that do not explain real mathematics learning. thus causing boredom and boredom, it is necessary to apply the development of game-based mathematics teaching materials. Where there are several game development methods that need to be applied in the classroom: math duel and ice breaking. So that by developing this game method, students' interest and motivation in learning will be more enthusiastic and there will be no more boredom in the classroom. As well as increasing students' self-confidence in dealing with mathematical tasks or problems and increasing students' ability to work in teams or socialize with classmates.